Angiographic Evaluation of Inflammation in Atopic Keratoconjunctivitis. (4th July 2018) - Steger, Bernhard; Romano, Vito; Kaye, Stephen B.
ABSTRACT: Purpose : Grading of disease activity in patients with atopic keratoconjunctivitis (AKC) is limited by intra- and inter-observer variability. The aim of this study was to identify angiographic parameters to help evaluate inflammation and disease activity. Methods : In 12 patients (4 with active, 2 with inactive AKC, and 6 controls), disease activity were assessed using a validated biomicroscopic grading scale. Imaging of upper tarsal conjunctiva was undertaken using color photography, fluorescein (FA) and indocyanine green angiography (ICGA). Results : Extravascular ICG leakage only occurred in patients with active disease (mean 84.6 ± 28.8 s) except in one patient with inactive disease but only after 6 min. Transepithelial leakage of fluorescein occurred in all patients with active AKC (mean 63.5 ± 17.8 s) but not in patients with inactive disease or controls. Conclusions : Conjunctival transepithelial leakage of fluorescein and extravascular interstitial accumulation of ICG may be useful markers of disease activity patients in AKC.